1999
DOI: 10.1109/78.757244
|View full text |Cite
|
Sign up to set email alerts
|

Repeated filtering in consecutive fractional Fourier domains and its application to signal restoration

Abstract: Abstract-Filtering in a single time domain or in a single frequency domain has recently been generalized to filtering in a single fractional Fourier domain. In this correspondence, we further generalize this to repeated filtering in consecutive fractional Fourier domains and discuss its applications to signal restoration through an illustrative example.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
53
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(53 citation statements)
references
References 18 publications
(27 reference statements)
0
53
0
Order By: Relevance
“…For this purpose, various time-frequency processing techniques (e.g. Hlawatsch et al, , 2000Erden et al, 1999;Hlawatsch and Kozek, 1994;McHale and Boudreaux-Bartels, 1993; Boudreaux-Bartels and Parks, 1986) can be used. In the following, results based on the time-frequency domain incision technique (Erden et al, 1999) will be presented.…”
Section: Application Of Tfca To the Analysis Of Multi-component Signalsmentioning
confidence: 99%
“…For this purpose, various time-frequency processing techniques (e.g. Hlawatsch et al, , 2000Erden et al, 1999;Hlawatsch and Kozek, 1994;McHale and Boudreaux-Bartels, 1993; Boudreaux-Bartels and Parks, 1986) can be used. In the following, results based on the time-frequency domain incision technique (Erden et al, 1999) will be presented.…”
Section: Application Of Tfca To the Analysis Of Multi-component Signalsmentioning
confidence: 99%
“…It is possible to further generalize these ®ltering con®gurations by using parallel and series arrangements together; such systems have been called generalized ®ltering circuits [1,2]. Fractional Fourier transform has found many applications in optics in general [8] and fractional Fourier transform-based ®ltering circuits have found applications in optical and digital signal and image restoration, signal and system synthesis, synthesis of mutual intensity distributions, and fast implementation of shift-variant linear systems [1,2,5,7].…”
mentioning
confidence: 99%
“…[2,5,7] fractional Fourier transformbased ®ltering con®gurations have been used for synthesizing linear space-variant systems, represented by some matrix T. It was shown that for many such systems encountered in various applications, it is possible to approximate the system with a multi-stage or multi-channel con®guration with acceptable mean square error, by using a small or moderate number (M) of stages or channels. Since the cost of implementing the fractional Fourier transform (optically or digitally) is similar to the cost of implementing the ordinary Fourier transform, this leads to a fast implementation of the space-variant system in question.…”
mentioning
confidence: 99%
See 2 more Smart Citations